HIV-1 viral blips are associated with repeated and increasingly high levels of cell-associated HIV-1 RNA transcriptional activity. (1st November 2021) - Suzuki, Kazuo; Levert, Angelique; Yeung, Julie; Starr, Mitchell; Cameron, Jane; Williams, Raffaella; Rismanto, Nikolas; Stark, Tayla; Druery, Dylan; Prasad, Salzeena; Ferrarini, Cristina; Hanafi, Imelda; et al.
Abstract : Objective: Some HIV+ patients, virally suppressed on ART, show occasional 'blips' of detectable HIV-1 plasma RNA. We used a new highly sensitive assay of cell-associated HIV-1 RNA to measure transcriptional activity in PBMCs and production of infectious virus from the viral reservoir, in patients with and without 'blips'. Design/methods: RNA and DNA extracted from cells in 6 ml of peripheral blood, from suppressed patients with one to two 'blip' episodes over the past 2 years of ART ( n = 55), or no 'blips' ( n = 52), were assayed for HIV-1 RNA transcripts and proviral DNA targeting the highly conserved 'R' region of the LTR. Follow-up samples were also collected. Purified CD4 + T cells were cultured with anti-CD3/CD28/CD2 T-cell activator to amplify transcription and measure replication competent virus. Results: HIV-1 RNA transcripts ranged from 1.3 to 5415 copies/10 6 white blood cells. 'Blip' patients had significantly higher levels vs. without blips (median 192 vs. 49; P = 0.0007), which correlated with: higher levels of inducible transcripts after activation in vitro, sustained higher HIV-1 transcription levels in follow-up samples along with increasing HIV-1 DNA in some, and production of replication-competent HIV-1. Conclusion: Viral 'blips' are significant reflecting higher transcriptional activity from the reservoir and contribute to the reservoir over time. This sensitive assay can be used in monitoring the size and activity of the HIV-1 reservoir and will be useful in HIV-1 cure strategies. Abstract : Supplemental Digital Content is available in the text